Pengaruh Brand Awareness dan Perceived Quality Terhadap Purchase Intention: Brand Loyalty Sebagai Variabel Mediasi - Alexandra Fenetta; Keni Keni (Universitas Tarumanagara, 2020)
The aim of this study are: first, to explore the effects of brand awareness, perceived quality and brand loyalty on purchase intention. Second, to explore the effects of brand awareness and perceived quality on brand loyalty. Third, to find out the effects of brand awareness and perceived quality on purchase intention if mediated by brand loyalty. The samples that are used in the research are 150 respondents in Jakarta conducted by convenience sampling. The data techniques are processed using structural equation modelling on software SmartPLS 3.2.8. The results of this research are: first, brand awareness and perceived quality do not have a positive impact on purchase intention, yet brand loyalty has a positive impact on purchase intention. Second, brand awareness and perceived quality have a positive on brand loyalty. Third, brand awareness and perceived quality have a positive impact on purchase intention if mediated by brand loyalty.